Substitution Policy and Generic Competition - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
I model the market for an active ingredient (with a brand-name drug and n differentiated generic versions) to study the effect of a substitution rule on prices and the extensive and intensive margin of generic competition. Both substitution rules with physician and patient veto decrease the brand-name price and shift market shares from the brand-name drug to the generics. A substitution rule with physician (patient) veto increases (decreases) generic prices and increases (decreases) the number of generic firms.
Keywords: I18; I11; L50; 330; substitution rule; generic competition